Gender difference in the association between lower muscle mass and metabolic syndrome independent of insulin resistance in a middle-aged and elderly Taiwanese population. (September 2017) - Ou, You-Ci; Chuang, Hai-Hua; Li, Wen-Cheng; Tzeng, I-Shiang; Chen, Jau-Yuan
Highlights: Lower muscle mass was associated with the risk of metabolic syndrome. MetS prevalence was present in 52.2%, 32.6%, and 19.6% of males and 50.0%, 29.4%, and 29.4% of females in the tertile groups. Both males and females in the lower muscle mass group had at least three significant metabolic risk factors compared to the middle- and higher-muscle mass groups. Preventing loss of muscle mass at older ages might have the potential to reduce MetS and females should be more aware of their loss of muscle mass problem. Abstract: Background: Loss of muscle mass was reported to be associated with metabolic syndrome (MetS), but little is known about the gender difference. Thus, the aim of this study was to evaluate the relationship between lower muscle mass and MetS and determine whether there was any gender difference or not. Methods: A total of 394 middle-aged and elderly Taiwanese adults (138 males and 256 females) were enrolled and completed our health survey. They were stratified into three groups according to appendicular skeletal muscle mass divided by weight. Participants distributed into the lower tertile were defined as people having lower muscle mass. MetS was defined using the Adult Treatment Panel III Asian diagnostic criteria. Multivariate logistic regression analysis was performed to assess the association between muscle and MetS. Results: We found an inverse association between MetS and muscle mass in both males and females. Participants with lower muscle mass had a higher risk of MetS in univariate analysis. The same results were observed when adjusted for age and when also adjusted for living condition factors. However, after additional adjustment for potential confounders and HOMA-IR, we only found it to be statistically significant in the female group (OR in male = 3.60; 95% CI = 0.62–20.83, p = 0.153; OR in female = 3.03; 95% CI = 1.16–7.94, p = 0.024). Conclusions: We examined the relationship between lower muscle mass and metabolic syndrome in a middle-aged and elderly Taiwanese population. We found that lower muscle mass was associated with the risk of metabolic syndrome in the aged, particularly in females.